Evaluasi Mutu Kukis Yang Disubstitusi Tepung Sukun (Artocarpus communis) Berbasis Minyak Sawit Merah (Msm), Tepung Tempe dan Tepung Udang Rebon (Acetes erythraeus) - Murni, Tri; Herawati, Netty; ', Rahmayuni (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The main material in making cookies is wheat flour and it also can be substituted by the using of sukun flour. The purpose of changing that flour is for getting the cookies whit the good content of nutrient and indirectly it also can decrease the depended of wheat flour which is import product and the content of gluten that has negative effect for the autism children. The purpose of this research is to learn about the formulation of making cookies that the main maetial is sukun flour based red palm oil, tempe flour, and shrimp flour rebon and to know about the receptive of panelist toward the cookies that is produced. This research is held experimentally by using Complete Randomized Design (CRD) consisting of four treatments and four replications. The treatmen that is hoal are SKA (wheat flour 100%, sukun flour 0%), SKB (wheat flour 66,6%, sukun flour 33,4%), SKC (wheat flour 33,4%, sukun flour 66,6%), SKD (wheat flour 0%, sukun flour 100%). Based on chemical analysis and assessment of organoleptic, the best cookies is SKD which has a moisture content (3,93%), ash content (2,34%), protein levels (10,30%), and it can be received by adult and children panelist. Key words: Cookies, wheat flour, and sukun flour